Repositioning Environmental NGOs: Either as non-Governmental or Private Sector Organizations - Annisa Qurrota A'yun; Saptaningtyas, Haryani (Journal of Social Development Studies, 2023)
Non-Governmental Organizations (NGOs) are an organization supported by an independent community, a voluntary and non-profit association. Their activities involve voicing the community and being a third party between the government and the private sector. With environmental issues starting to change and being damaged due to inappropriate government policies, environmental NGOs play an essential role in balancing this condition. This article will discuss the position of NGOs during environmental issues that hit Indonesia observed by two environmental organizations, WALHI and KruHA, taking official information published on their websites and social media. The analysis uses discourse text analysis, deconstruction of meaning or communication messages on official information. This paper argues that not all non-profit organizations act of WALHI and KruHA are NGOs in non-profit organizations. They are outside the government and private sector, the so-called “third sector” that plays a role in the right to water and environmental sustainability. Though they are the same as non-profit NGOs, their movement mechanism is different.